Genomic Signatures After Five Generations of Intensive Selective Breeding: Runs of Homozygosity and Genetic Diversity in Representative Domestic and Wild Populations of Turbot (Scophthalmus maximus) - Aramburu, Oscar; Ceballos, Francisco; Casanova, Adrián; Le Moan, Alan; Hemmer-Hansen, Jakob; Bekkevold, Dorte; Bouza, Carmen; Martínez, Paulino (Frontiers in Genetics, 2020)
Massive genotyping of single nucleotide polymorphisms (SNP) has opened opportunities for analyzing how selection shapes genomes. Artificial/natural selection leaves genomic signatures associated with selective sweeps around the responsible locus. Strong selective sweeps are often identified by lower genetic diversity than the genomic average and/or islands of runs of homozygosity (ROHi). We conducted an analysis of selective sweeps in turbot (Scophthalmus maximus) using two SNP datasets from a Northeastern Atlantic population (36 individuals) and domestic broodstock (46 individuals). Twenty-six families (~40 offspring per family) from this broodstock and three SNP datasets applying differing filtering criteria were used to adjust ROH-calling parameters. The best-fitted genomic inbreeding estimate (FROH) was obtained by the sum of ROH longer than 1Mb, using a 21,615 SNP panel, a sliding window of 37 SNPs and one heterozygous SNP per-window allowed. These parameters were used to obtain the ROHi distribution in the domestic (49 ROHi) and wild populations (0 ROHi). Regions with higher/lower genetic diversity within each population were obtained using sliding windows of 37 SNPs. Those regions were mapped in the turbot genome against QTL-associated markers (Quantitative Trait Loci) and outlier loci for domestic/natural selection to identify putative selective sweeps. Out of the 319 and 278 windows surpassing the suggestive pooled heterozygosity thresholds (ZHp) in the wild and domestic population, respectively, 78 and 54 were retained under more restrictive ZHp criteria. A total of 116 suggestive windows (19 genomic regions) were linked to QTL for production traits, or outliers for divergent/balancing selection. Twenty-four of them (3 genomic regions) were retained under stricter ZHp thresholds. Eleven QTL/outlier markers were exclusively found in suggestive regions of the domestic broodstock, 7 in the wild population and one in both; one (broodstock) and two (wild) of those were found in significant regions retained under more restrictive ZHp criteria in the broodstock and the wild population, respectively. Genome mining and functional enrichment disclosed relevant genes and pathways related to aquaculture target traits, including growth and immune-related pathways, metabolism and response to hypoxia, showcasing how this atlas can be a valuable resource to look for candidate genes related to selection in turbot populations.